À redação do Diário: uma análise das cartas dos leitores do Diário de S. Paulo - Barros, Isabela Pereira (2009)
The research "To the Press Office of the Diary - A review of the letters from readers of the Diário de S. Paulo" aims to conduct a semiotic analysis of the discourse of the newspaper dai1y readers of the newspaper and further understanding, through semiotic examination, the relation between those and the newspaper. The choice of the Diário is justified by the popular character of the newspaper and its experience in this field through the years (125). Hence, By maping these readers reactions, their points and requirements it will be possible to understand what place has the newspaper achieved in their lives. Additionally, it aims to analise if the responses of the readers make new topics emerge on the daily draft of the newspaper. The concept of immersive reader will be used in this research as a fundamental point of analisis of the point of views of the readers who found themselves embraced by a new concept of reading, marked by the interactivity of the ciber space.Thus, the comparison between the attitude of readers of a newspaper printed and readers of blogs on the intemet will be crucial to this work as it examines the changes brought by intemet and the immersive lector that it introduces. The corpus of this research is composed by a selection of letters to the Diário de S. Paulo. It will be considered the letters published in 2007, 2008 and 2009 (from January to March). The reactions of the readers after cases of great commotion, related to religion, sexuality and policies. The methodology involves the discourse analyisis of the contents of the letters and also the newspaper that are connected, as well as bibliographic and documentary literature. Among the authors selected as main references are Roland Barthes, Eugênio Bucci, Lúcia Santaella and José Luiz Fiorin